Total Quality Management (TQM) in Bpjs Patient Services in MM Dunda Limboto Hospital - Widya Kurniati Mohi; Ramli Makmur (Pusat Studi Pembangunan dan Pemberdayaan, 2021)
This study aims to determine and analyze how Total Quality Management in BPJS Patient Services at MM Dunda Limboto Hospital. This research is a descriptive research with a qualitative approach. Several indicators used are Commitment, Communication, Cooperation, Criticsimn. Based on the results of research and discussion related to the indicators of criticism in question, it was concluded from several informants that the hospital should better understand the situation in the hospital with the existence of a suggestion box, because which patients think about that suggestion, it is better like the advice of the patient by filling in a draft that was delivered directly by the officer to be filled in so that the evaluation material was available and quickly knew the response from the patient but the patient was getting better.